Impact of Prehospital Mobile Intensive Care Unit Intervention on Mortality of Patients with Sepsis - Jouffroy, Romain (Turk J Anaesthesiol Reanim, 2019)
OBJECTIVE: The outcome of sepsis relies on the early diagnosis and implementation of appropriate treatments. For management of out-of-hospital patients with sepsis, prehospital emergency services, named Service d’Aide Médicale d’Urgence (SAMU) in France, dispatch to the scene an emergency mobile team (EMT) or a mobile intensive care unit (MICU) based on the patient’s severity. Therefore, patients are admitted to the emergency department (ED) or to the intensive care unit (ICU). The impact of MICU intervention on patient’s prognosis remains unclear. The aim of the present study was to describe the impact of MICU intervention on mortality on day 28 (D28) of patients with sepsis. METHODS: We performed a retrospective study on patients with sepsis managed by prehospital teams, MICU or EMT, before admission to the ED or ICU. The primary outcome was mortality on D28. RESULTS: The SAMU received 30,642 calls during the study period with 140 patients with suspected sepsis. The suspected origin of sepsis was mainly pulmonary for 78 (55%) patients. Thirteen (9%) patients died on D28, 12 in the ED and 1 in the ICU. Two patients were admitted to the hospital by a MICU. After adjusting for confounding factors, the relative risk of mortality on D28 for patients admitted to the hospital by a MICU was 0.40. CONCLUSION: We describe an association between MICU intervention and mortality on D28. MICU intervention for out-of-hospital patients with sepsis is associated with 60% reduced mortality on D28. Larger studies are needed to confirm the impact of the intervention of MICU on mortality of patients with sepsis.